KERAGAMAN JENIS RAYAP PADA HUTAN SEKUNDER DAN AGROFORESTRI DI TAMAN NASIONAL LORE LINDU, SULAWESI TENGAH - Zulkaidhah Zulkaidhah; Musyafa Musyafa; Soemardi Soemardi; Suryo Hardiwinoto (Agroland: Jurnal Ilmu-ilmu Pertanian, 2013)
This study aims to assess the structure and communities of termite caused by changes in land use. The research was conducted from December 2011 to January 2013, Implemented in Lore Lindu National Park area around the village of grace Palolo Sub district, Sigi Regency. The observation of termites was conducted using transect method. Parameters observed were environmental parameters, soil physical and chemical characteristics. The total diversity of termite species found was 15. Diversity of trees, nekromas, and the amount of litter that is higher in secondary forest than in agroforestry cause soil water content and moisture become higher in secondary forests and there fore contributes toan increase in soil organic matter content. Key Words : Agroforestry, diversity of  termite, forest use change, secondary forest.